Dissecção virtual e morfometria do girino Thoropa miliaris usando o algoritmo de recuperação de fase em imagens 3D obtidas com luz síncrotron - Silva, Gabriel Fidalgo Queiróz da (2019)
The use of amphibians as experimental models has great application in Biology. Studies of the natural history of amphibians have clearly identified attributes that make them suitable for experimental manipulations, showing results on their diversity and data on ecological systems. The use of tadpoles in scientific research is very important because approximately 75% of the cataloged amphibian species have this larval stage in an analogous way. The objective of this work was to present the first non-invasive and highresolution morphometric analysis of tadpoles of the Brazilian amphibian Thoropa miliaris, using synchrotron microtomography, where a protocol was created to acquire images of these samples in a liquid solution. It was used the IMX beamline, in the Brazilian Synchrotron Light Laboratory, and SYRMEP beamline, in the Elettra Synchrotron (Italy), both of which have remarkable characteristics for biomedical applications. In order to better visualize the internal structures of the animal, the in-line phase-contrast technique was used, where the phase-retrieval algorithm was used together with the filtered backprojection reconstruction algorithm. The use of these imaging and reconstruction techniques allowed access to information on the morphology and development of the internal structures of Thoropa miliaris, providing data regarding their development, from the observation of these tissues.